Improving Teachers' Attitude Towards, Understanding of, and Competence in Inclusive Education - . Sunardi; . Maryadi; . Sugini (International Conference on Education and Language (ICEL), 2013)
This previously UNESCO initiated policy of inclusive education has been adopted by the Indonesian government since 2003. As a new policy, inclusion will require many changesin the existing system of education which tends to be segregative. This research investigated the effects of a workshop in inclusive education on parents attitudes, teachers’ competence and knowledge.The subjects of the study were 50 parents and 50 teachers of 25 primary schools from 25 subdistricts in the district of Wonogiri.  They took part in a twoday workshop in inclusive education using active learning modes of presentation. Teachers’ knowledge was measured using a written test, while parents’ attitudes and teachers’ competence were measured using likert type scales.The results showed that:1        The mean score of parents’ attitudes before workshop was 137,26 (SD=17.383)  (already above the mid score of 105) which meant that they showed positive attitudes), and the mean score after workshop was 148,46 with a standard deviation of 15,439. A t-test for correlated means resulted in a p=0.000, which meant that the score improvement was highly significant.2        The mean score of teachers’ competence before workshop was 334,82 (SD= 69,857) and the mean score after workshop was372,56 (SD=72,505). Both means were below the mid score of 375, indicating low teachers’ competence. A t-test for correlated means resulted a p value of=0.000, meaning that the score improvement was highly significant.3        The mean score of teachers’knowledge before workshop was 57.60and the mean score after workshop was 67.36, both were below the mastery criteris of 70. A T-test for correlated means resulted a p value of 0,00,indicating a signicant improvement of knowledge.